Adolescents' attitudes to the COVID-19 vaccination. Issue 7 (11th February 2022) - Wong, W.H.S.; Leung, D.; Chua, G.T.; Duque, J.S.R.; Peare, S.; So, H.K.; Chan, S.M.; Kwan, M.Y.W.; Ip, P.; Lau, Y.L.
Abstract: Vaccines against COVID-19 are now available for adolescents in Hong Kong but vaccine hesitancy is a major barrier to herd immunity. This survey study explores Hong Kong adolescents' attitudes towards the COVID-19 vaccination. 2609 adolescents from across Hong Kong completed an online survey focused on the intent to vaccinate and the reasons for their choice. 39% of adolescents intended to take the COVID-19 vaccination and significant factors for this decision include: having at least one parent vaccinated, knowing somebody diagnosed with COVID-19 and receiving the influenza vaccine. Adolescents' major concerns were either the safety and efficacy of the vaccine or the risk of infection. This study has proved that even in adolescents the vaccine hesitancy model is prominent with adolescents' intentions highly related to confidence in the vaccine and perception of disease risk. Future interventions should target these specific concerns to ensure adolescents are well educated to overcome vaccine hesitancy.